Exploring the Critical Barriers Towards Women Participation in Surveying and Geo-Informatics Practices - Gbenga, Precious Oluwatofunmi; Bello, Abdulkabir Opeyemi; Olaniyi, Abdulmalik Mobolaji; Idris, Abdullahi (Journal of Multidisciplinary Research Advancements, 2023)
Surveying and geo-informatics stand as a significant field at the intersection of science, technology, and spatial management, playing a crucial role in informing decision-making across various industries. However, the surveying and geo-informatics field suffers from the underrepresentation of women professionals. This underrepresentation carries significant implications hindering diversity of knowledge and skills. In order to build a more inclusive and equitable professional environment, the study aims to identify and analyse the identified barriers to offer insight and strategies to enhance women's participation. Data were gathered using a mixed-methods (sequential exploratory) approach, which included interviews and structured questionnaires (five Likert scale) with professionals in the field. Twenty-five participants and 138 responses were considered for the study. Statistical tests such as Cronbach's Alpha, mean ranking, one sample t-test, Chi-square, Kruskal Wallis, and factor analysis were conducted to investigate the significance and relationship between the identified barriers. The result shows that the participation of women in the surveying and geo-informatics field is low. Similarly, the study shows that the barriers are critical to the participation of women in the field, considering their significance level. In addition, a rotation of the component matrix reveals three dimensions: equity and inclusion, career advancement and assistance, and gender equality and empowerment. These factors offer a thorough foundation for comprehending the many difficulties women in the field encounter. The study developed various strategies tailored to mitigate each barrier component. The findings of this study add to the body of knowledge on gender differences in surveying and geo-informatics practises and offer policymakers, organisations, and stakeholders valuable insights. Eliminating these obstacles will improve gender diversity, encourage inclusivity, and fully utilise the talents of women, ultimately resulting in a more innovative and sustainable surveying and geo-informatics profession in Nigeria.